2010
DOI: 10.1007/s10640-010-9412-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Diversity of Large Wildlife Species on Financial Benefits to Local Communities in Northwest Namibia

Abstract: Africa, Biodiversity, Community-based conservation, Community ecology, Ecosystem services, Diversity, Ecotourism, Stability, Wildlife,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
32
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 24 publications
3
32
0
Order By: Relevance
“…Of course, most recreation activities depend on built infrastructure, accessibility, and other factors, but the fundamental importance of ecological conditions has been widely demonstrated (76)(77)(78)(79). For a specific example, Fuller et al (77) surveyed visitors to urban/suburban parks and found that psychological well-being (gauged by factors derived from park visitor's reports, including reflection, identity, and attraction) was positively correlated with the species richness and habitat diversity in the park.…”
Section: Scientific Foundations For Integrating Cultural Servicesmentioning
confidence: 99%
“…Of course, most recreation activities depend on built infrastructure, accessibility, and other factors, but the fundamental importance of ecological conditions has been widely demonstrated (76)(77)(78)(79). For a specific example, Fuller et al (77) surveyed visitors to urban/suburban parks and found that psychological well-being (gauged by factors derived from park visitor's reports, including reflection, identity, and attraction) was positively correlated with the species richness and habitat diversity in the park.…”
Section: Scientific Foundations For Integrating Cultural Servicesmentioning
confidence: 99%
“…This is partly because the cost of conservation has been displaced on to people for whom conservation is not their first priority. There are certainly instances where conservation efforts have yielded tangible benefits to local populations (see, 1 Six international conventions are argued to have a primary focus on biodiversity issues: the Convention on Biological Diversity (year of entry into force: 1993), the Convention on Conservation of Migratory Species, the Convention on International Trade in Endangered Species of Wild Fauna and Flora (1975), the International Treaty on Plant Genetic Resources for Food and Agriculture (2004), the Ramsar Convention on Wetlands (1971) and the World Heritage Convention (1972). for example, Naidoo et al 2011). Yet over all very few conservation projects in developing countries have had positive impacts on rural incomes (Wells and Brandon 1992;IUCN 2002;Tallis et al 2008).…”
mentioning
confidence: 99%
“…Others argue that CBNRM clearly has the potential -realized in some projects -to improve conservation outcomes and bring financial benefits to local communities Jones and Weaver 2009;Naidoo et al 2011;Taylor 2009) and to shift local attitudes about conservation from negative to positive (Mbaiwa and Stronza 2011). This potential is most likely to be realized when projects get the incentives right (Suich 2013).…”
Section: Craft In the Context Of Community-based Conservationmentioning
confidence: 99%